2014
DOI: 10.3389/fnbeh.2014.00330
|View full text |Cite
|
Sign up to set email alerts
|

The Body Action Coding System II: muscle activations during the perception and expression of emotion

Abstract: Research into the expression and perception of emotions has mostly focused on facial expressions. Recently, body postures have become increasingly important in research, but knowledge on muscle activity during the perception or expression of emotion is lacking. The current study continues the development of a Body Action Coding System (BACS), which was initiated in a previous study, and described the involvement of muscles in the neck, shoulders and arms during expression of fear and anger. The current study e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
(102 reference statements)
0
20
0
Order By: Relevance
“…Why did participants look towards fearful faces, but avert their gaze away from angry faces, in the absence of awareness? As mentioned in the Introduction, under awareness these two threat-related emotions have differential perceptual consequences (Kret et al, 2013b; Marsh et al, 2005; Springer et al, 2007; Huis In 't Veld et al, 2014) and may be mediated by different neural pathways (Luo et al, 2007). In the absence of awareness, before this study, there had been only circumstantial evidence for differential processing of angry and fearful faces according to the time they take to break into awareness (Yang et al, 2007; Milders et al, 2006; Troiani et al, 2014; Jusyte et al, 2015; Zhan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why did participants look towards fearful faces, but avert their gaze away from angry faces, in the absence of awareness? As mentioned in the Introduction, under awareness these two threat-related emotions have differential perceptual consequences (Kret et al, 2013b; Marsh et al, 2005; Springer et al, 2007; Huis In 't Veld et al, 2014) and may be mediated by different neural pathways (Luo et al, 2007). In the absence of awareness, before this study, there had been only circumstantial evidence for differential processing of angry and fearful faces according to the time they take to break into awareness (Yang et al, 2007; Milders et al, 2006; Troiani et al, 2014; Jusyte et al, 2015; Zhan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Angry faces indicate direct threats (a person with an angry expression looking directly at the observer) leading to avoidance (Schmidt et al, 2012; Marsh et al, 2005) or freezing (Roelofs et al, 2010) responses. When looking at angry faces observers show a stronger startle reflex (Springer et al, 2007), stronger activation of the torso muscles (Huis In 't Veld et al, 2014), widening of the pupils (Kret et al, 2013b), and higher activation in brain areas associated with defense preparation (Williams et al, 2005; Pichon et al, 2009; Kret et al, 2011) than when looking at fearful faces. Threat processing is considered to evolve along two distinctive neuronal pathways, a fast sub-cortical and a slower cortical route (LeDoux, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that it is important to animate human-like virtual characters and program robots with human-like motion data. Several EMG studies by Huis in ‘t Veld et al (2014a , b ) suggested that specific muscle groups are used for the bodily expressions of emotion in humans. This information, together with motion capture data could be used to improve modeling of biological movements for virtual agents and robots.…”
Section: Action Perception In Virtual Characters and Robotsmentioning
confidence: 99%
“…A few used Laban movement analysis or its most known components: Effort and Shape (Levy and Duke, 2003 ; Gross et al, 2010 , 2012 ; Crane and Gross, 2013 ). Yet others characterized the movements based on the specific muscles that are activated (Huis In 't Veld et al, 2014a , b ), or used kinematic variables such as movement duration, velocity, acceleration, joints displacement (range of motion), and joint coordination (Pollick et al, 2001 ; Sawada et al, 2003 ; Roether et al, 2009 ; Gross et al, 2010 , 2012 ; Barliya et al, 2013 ). Although these studies were able to discriminate among the different emotions expressed in movement, they used different coding schemes, making it difficult to compare outcomes across studies and to build a comprehensive description of the associations between certain motor characteristics of body movements and specific emotions (Gross et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%